Obstructive Sleep Apnea Syndrome Associated with Atrial Fibrillation in Adult Patients: A Systematic Review and Meta-Analysis - Carrasco, Oswaldo Gómez; Gómez Carrasco, Bryam Martin; Gómez, Gerard; Espinoza-Rojas, Rubén; Orihuela-Manrique, Eder Jesús; García-Lara, Rosa Angélica; Loayza-Castro, Joan A.; Zeñas-Trujillo, Gianella Zulema; Vera-Ponce, Víctor Juan; Cruz-Vargas, Jhony A. De La (International Journal of Statistics in Medical Research, 2023)
Introduction: Obstructive sleep apnea syndrome (OSAHS) is a common disease. However, its diagnosis and treatment are underestimated. The main reason is that the upper airway completely or partially collapses, leading to repeated sleep apnea episodes. In addition, atrial fibrillation(AF) is the most frequent arrhythmia in the world, these two entities may be related and are important public health problems. Objective: To determine the association between obstructive sleep apnea syndrome and atrial fibrillation in adult patients. Materials and Methods: A systematic review and meta-analysis of observational studies that associate obstructive sleep apnea syndrome and atrial fibrillation was carried out. The search was carried out in 4 databases: PUBMED, Web of Science, Embase, Scopus. Results: Eight studies were included (n=562241). A significant association was found between obstructive sleep apnea and atrial fibrillation (OR: 1.38; 95% CI 1.24 to 1.54). In addition, low heterogeneity was found between studies I2: 13%. Conclusions: It was found that obstructive sleep apnea and atrial fibrillation are significantly associated.